Effect of a nutritional immunomodulator in dry cows heat stressed with an electric blanket model - L.T. Casarotto; L. Cattaneo; K.M. Glosson; B.D. Humphrey; J.D. Chapman; G.E. Dahl (Journal of Dairy Science)
ABSTRACT: Heat stress in the dry period reduces yield and health in the next lactation. Previous work indicates that feeding OmniGen AF (OMN; Phibro Animal Health) mitigates the detrimental effects of heat stress. Electric blankets (EB) can induce heat stress in lactating cows, but EB have not been used with dry cows. The objectives of this study were to explore efficacy of the EB on cows during the dry period, as well as to examine the effect of feeding OMN to heat-stressed cows. We hypothesized that EB would increase body temperature in dry cows and OMN would ameliorate the effects of heat stress. Fifty Holstein cows were housed individually in a tie-stall barn upon dry-off ∼48 d before expected calving (223.7 ± 5 d carried calf) and cows were fitted with EB or no blanket (NB). Within EB and NB, cows were fed OMN (OMN; 56 g/d) or did not receive OMN (CON), which resulted in a 2 × 2 factorial of 4 treatments: NB-CON, EB-CON, NB-OMN, and EB-OMN. Throughout the dry period, DMI, water intake, and respiration rate (breaths/min) were measured daily, and rectal temperature was measured twice daily. After calving, all the cows were cooled and managed identically, and milk yield and composition were measured at each milking. Use of EB increased rectal temperature and respiration rate relative to NB regardless of diet; OMN treatment did not affect rectal temperature or respiration rate. Dry matter intake was reduced by over 1 kg/d with EB, and OMN feeding reversed this effect. Water intake increased with EB relative to NB, but OMN was without effect. Treatment did not affect gestation length. In early lactation, EB cows produced 6 kg/d less ECM relative to NB, and OMN reversed the effect on milk yield in EB cows. These data support the hypotheses that EB induce heat stress in dry cows and that OMN effectively mitigates the detrimental effects of heat stress in the dry period.